2009
DOI: 10.1002/glia.20858
|View full text |Cite
|
Sign up to set email alerts
|

Neurosphere cell differentiation to aldynoglia promoted by olfactory ensheathing cell conditioned medium

Abstract: Cells from central nervous system with morphology similar to radial glia and properties intermediate between astrocytes and Schwann cells were called growth-promoting glia or aldynoglia. These cells are present in adult brain olfactory bulb, hypothalamus, hypophysis, pineal gland and in the developing brain, and spinal cord (Cameron and Rakic (1991) Glia 4:124-137; Gudiño-Cabrera and Nieto-Sampedro (2000) 30:49-63). We report now that neurosphere cells, abundantly generated from E15 rat or E13 mouse corpus str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 124 publications
1
22
0
Order By: Relevance
“…This discrepancy between in vitro and in vivo findings could be due to several reasons. Since CNS Schwannlike cells have been so far only partially characterized in vitro (Donzel-P erez et al, 2009;Orlando et al, 2008), it is not clear whether the used purification protocol supported the isolation of a representative cell population. However, the fact that not a single CDV-positive Schwann-like cell expressing p75 NTR was found in vivo clearly argues against this notion.…”
Section: Factors Controlling the In Situ Generation Of Adult Canine Smentioning
confidence: 99%
“…This discrepancy between in vitro and in vivo findings could be due to several reasons. Since CNS Schwannlike cells have been so far only partially characterized in vitro (Donzel-P erez et al, 2009;Orlando et al, 2008), it is not clear whether the used purification protocol supported the isolation of a representative cell population. However, the fact that not a single CDV-positive Schwann-like cell expressing p75 NTR was found in vivo clearly argues against this notion.…”
Section: Factors Controlling the In Situ Generation Of Adult Canine Smentioning
confidence: 99%
“…We have shown in culture that neurosphere-derived cells are able to differentiate into a type of axonal-growth-promoting ensheathing glia, named aldynoglia (Gudino-Cabrera and Nieto-Sampedro, 2000; Doncel-Pérez et al, 2009). As such glia and neurons positive for GFP expression (Figure 3) facilitated the tracking of transplanted cells into the brain.…”
Section: Resultsmentioning
confidence: 99%
“…Striatum from C57BL/6 mice, transgenic for the GFP gene [strain C57BL/6-TgN(ACTbEGFP)1Osb] (Okabe et al, 1997) were used to obtain NSCs constitutively expressing GFP as previously reported (Doncel-Pérez et al, 2009) (step 1). Neurospheres, isolated from E13 striatum, were incubated in NB27 medium (step 2), a mix of Neurobasal medium and B27 supplement (GIBCO, Scotland, UK) containing human bFGF (10 ng/mL) and EGF (20 ng/ml; Peprotech, New Jersey, USA), L-glutamine (0.5 mM), L-glutamate (25 mM), penicillin (100 U/mL), streptomycin (0.1 mg/mL) (all from Sigma-Aldrich), and fungizone (2.5 g/mL; Invitrogen, Madrid, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, OBEC-conditioned medium was used to elicit neuritogenesis in vitro via the cocultures of neurons and EC (Kafitz & Greer, 1999;Sonigra et al, 1999;Wang et al, 2003), and more recently, we and other groups have been studying the capacity of the OBECconditioned medium to induce and direct in vitro differentiation from neural stem cells (Rojas-Mayorquín et al, 2008;Zhang et al, 2008;Doncel-Pérez et al, 2009) or even from other stem cells (Wang et al, 2007). Given that OBECs are able to produce, secrete and also respond to a variety of growth factors (Table 2) and because the OB displays constant neuroglial replacement (Altman, 1969;Graziadei and Monti Graziadei, 1978), it is therefore reasonable to propose that the OBEC could induce its own differentiation from stem cell precursors located in the OB in vivo, or even that of other stem cells in vitro (Rojas-Mayorquín et al, 2008;.…”
Section: Obec-conditioned Medium Is a Suitable Model For Inducing Andmentioning
confidence: 99%